Editor’s note: Read the world to write the future: Critical education to address contemporary issues - Castellví Mata, Jordi (Universitat Autonoma de Barcelona, 2022)
Social sciences education and language and literature education are bonded by a strong link that goes back to the origins of both areas. The development of critical thinking and critical literacy has been -and continues to be- one of the key elements of these research lines. Both have always had on the horizon a global, reflective, and critical citizenship education, capable of dismantling hate narratives present in the media and on social networks by reading beyond the lines and the sources of information, analyzing texts, images, videos, and other cultural products in order to identify ideologies and be able to understand and face past and current social issues, projecting themselves into the future
Keywords: critical literacy; counter-hate speech; global citizenship; social sciences education; Scopus